Literature Study: Analysis of Student Learning Independence and Student Learning Outcomes in Online Learning in Elementary Schools : Studi Literatur: Analisis Kemandirian Belajar Siswa Dan Hasil Belajar Siswa Pada Pembelajaran Daring Di Sekolah Dasar - Rafida Putri Widiyanti; Enik Setiyawati (Academia Open, 2022)
This study has a research objective, namely to find out the results of a literature review about the learning independence of elementary school students in online learning and to find out the results of a literature review regarding the learning outcomes of elementary school students in online learning. The research method used in this study is to collect articles, journals and books that are in line with the title of the research used by the researcher. So the results of this study are learning independence is one of the factors that determine student success in learning, so that learning independence is important for anyone, especially a student if he wants to achieve success in his life. From the emergence of independent learning in students, it can affect the learning outcomes obtained by students in the learning process, because learning outcomes are assessments made by teachers in learning that can show learning outcomes that can be used as guidelines by teachers to see students' understanding of the material given during learning .Keywords- Independent Learning; Learning outcomes; Online Learning.